Implementasi Fuzzy Inference System (FIS) Pada Metode Tsukamoto Dalam Peramalan Produksi Roti (Studi Kasus: Harum Bakery) - Meriza Nadhira Atika Surya; Nurul Hidayat; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Nowadays, bread has became a trend of food that is much favored not only by foreign residents, but also by the people of Indonesia. The problem in Harum Bakery is still having difficulty in the production of bread because the method used is still conventional because the calculation used is still limited to its own estimates so that the bread produced sometimes the amount of excess or lack. In this study, the method used in this study is Fuzzy Inference System (FIS) Tsukamoto. This method is good enough to be used in the case of forecasting a production. From the system with the FIS method Tsukamoto, is expected to help the company so as to minimize losses and optimize profits. The results obtained were then evaluated by the RMSE method, the lowest error rate during the tests using 20 training data on the sweet bread with the result for sweet bread that is 69,9957142, and the bread cake is 8,77496439. Then for forecasting, the best result is using 60 training with RMSE value of 3.47850543.